Seasonal abundance and bio-efficacy of different insecticides against castor semilooper on castor (Journal of Applied and Natural Science, 2016)
The present study was conducted at Chaudhary Charan Singh Haryana Agricultural University, Hisar, Regional Research Station, Bawal, Haryana (India). The larvae of castor semilooper remain active from 30th standard weeks to 47th standard weeks. The maximum larval population was recorded on the 32th standard week (6.1 larvae per plant) and 38th standard meteorological weeks (6.2 larvae per plant) due the high rainfall, 158 and 120 mm, during these weeks, respectively. Correlation indicates that minimum temperature, evening relative humidity and rainfall exhibited a positive relationship (r- 0.588, 0.577 and 0.650) with the larval population. Bio-efficacy of four insecticides with different doses was tested against A. janata infesting castor crop. One day after spraying thiodicarb @ 468 g proved best toxicant followed by thiodicarb @ 375 g, deltamethrin @ 11.2 g, deltamethrin @ 10.5 g, quinalphos @ 250 g, quinalphos @ 200 g, novaluron @ 100 g and novaluron @ 75 g. At three days after spraying, it was found that novaluron @ 100 g was the most effective followed by novaluron @ 75 g, thiodicarb @ 468 g, deltamethrin @ 11.2 g, thiodicarb @ 375 g, deltamethrin @ 10.5 g, quinalphos @ 250 g and quinalphos @ 200 g. At seven days after spraying novaluron @ 100 g proved to be best toxicant followed by novaluron @ 75 g, thiodicarb @ 468 g, thiodicarb @ 375 g, deltamethrin @ 11.2 g, deltamethrin @ 10.5 g, quinalphos @ 250 g and quinalphos @ 200 g. Novaluron 100 g was the overall most effective with 75.97 mean per cent reduction in larval population.